(untitled) (Bangladesh Journal of Microbiology, 2021)
Antimicrobial activity of ethanol extracts of betel leaf (Piper betle L.) and areca nut (Areca catechu) against six food borne enteric pathogens viz. Staphylococcus aureus (ATCC 25923), Staphylococcus epidermidis (icddr,b), Salmonella typhimurium (AIM-40, icddr,b), Escherichia coli (ATCC 25922), Escherichia coli O157:H7 (ATCC 12079) and Bacillus cereus (ATCC 12079), and four oral pathogens such as isolates 1 & 2 of each of the two bacteria viz. Staphylococcus sp. and Pseudomonas sp. was investigated. Ethanol extract of betel leaf produced highest zone of inhibition (18.0 ± 1.91 mm) against Staphylococcus epidermidis (icddr,b) whereas that of areca nut produced highest zone of inhibition (15.0 ± 0.816 mm) against Staphylococcus aureus (ATCC 25923). But no inhibition was found against Salmonella typhimurium (ATCC AIM-40, icddr,b), Escherichia coli (ATCC 25922), and Escherichia coli O157:H7 (ATCC 12079) by the Ethanol extract of betel leaf. The MIC and MBC values of both ethanol extracts indicated that Gram positive organisms were more susceptible than Gram negative organisms. Highest antimicrobial activity of ethanol extracts of betel leaf was found against the isolate 1 of Staphylococcus sp. (16.5±0.5) and that of areca nut was recorded against the isolate 1 of Staphylococcus sp. (12.0±0.5) and the isolate 2 of Pseudomonas sp. (12.0±0.5). Present study reveals the potentials of both the extracts to inhibit food borne enteric and oral pathogens that could be used as food preservatives to prevent the food borne illness as well as for maintaining the oral and gut health. Bangladesh J Microbiol, Volume 38, Number 1, June 2021, pp 15-19